Comparison of Lagostomus maximus amelogenin gene (AMELX) with other mammals - Espinosa, Maria Beatriz (2016)
The aim of this study was to compare the Lagostomus maximus AMEL sequence to assess their similarity with the AMEL genes from other mammals. Previously we reported a sequence of the AMEL gene of Lagostomus maximus which corresponds to the intron 3 of the human sequence for AMELX (AMEL on the X chromosome). The comparisons made, by the use of the algorithm provided by the NCBI (Basic Local Alignment Search Tool: BLAST) allowed us to find out the possible similitude between the sequence corresponding to the AMEL gene of some species of mammals with the AMEL sequence of Lagostomus maximus. We believe that the reported sequences for this gene should be studied further.